STATE MECHANISMS FOR THE IMPROVEMENT OF INNOVATIVE ACTIVITY ON RAILWAY TRANSPORT - D. Kregel (Publishing House of the State University of Management, 2018)
The article deals with the state mechanisms of stimulating innovative activity in railway transport. The importance of the railway industry and the priority role of companies with state participation in its development determines the increased role of the state in the formation of mechanisms to stimulate innovation in transport. The article considers the main factors that are associated with the evolution of incentive mechanisms for innovation; the classification of incentive mechanisms for innovative activities in rail transport is presented. The main tasks of the state on stimulating activity in the sphere of innovations are also highlighted. The author made a conclusion on the need to improve the activities of state authorities in the sphere of stimulating research and innovation activities at all levels of government.